Perancangan Produk Rak Sepatu dengan Memanfaatkan Limbah Tutup Botol Plastik untuk Mendukung Sustainable Development Goals (SDG 12) - Audy Aprillia; Prameswari R.J; Alif Muhammad Shaquille; Yeni Nurhasanah (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Plastic waste, particularly bottle caps, poses a significant environmental challenge due to its slow degradation rate. This study aims to design a functional shoe rack utilizing plastic bottle cap waste to support Sustainable Development Goals (SDG 12: Responsible Consumption and Production). The product development process employed the Quality Function Deployment (QFD) method to translate consumer needs into measurable technical specifications. Concept selection was evaluated using the Pugh Matrix, while financial feasibility was analyzed through the Break Even Point (BEP) approach. The research resulted in an optimal shoe rack design measuring 53x32x37 cm, weighing 1.5 kg, and featuring additional side hangers for socks. The production process involves shredding, molding with resin, cutting, and assembling, with a total duration of 367.03 minutes. Financial analysis indicates that the business reaches the break-even point at a minimum production of 2 units or a total sales value of Rp227,272. This research demonstrates that integrating industrial engineering methods into plastic waste management can produce functional, durable, and economically viable products.